RUMUSAN STRATEGI PEMASARAN DALAM PENJUALAN PRODUK DENGAN METODE SWOT DAN QSPM (Quantitative Startegic Planning Matrix) (Studi Kasus CV. Bimanda Elektronik Pekanbaru) - Ahmad Nurul Sabry (Fakultas Teknik UMRI, 2020)
CV. Bimanda Elektronik is a company engaged in the sale of electronics. Based on a preliminary survey, which is a decline in sales every month in the 2019 period. The marketing strategy used by CV. Bimanda Elektronik at the moment is using word of mouth promotion. This research was conducted to identify and analyze the company's internal and external environmental factors that affect the marketing strategy of electronic product marketing and to design marketing strategies using the SWOT and QSPM methods. Based on the objectives, the company's main strength is the competitive market price with a score of 249 and the company's main weakness is not using a website or database system with a score of 0.092. While the main opportunity that the company has is the high consumer loyalty to the company's products with a score of 0.358 and the company's main threat is the number of substituted products with a score of 0.311. By using the SWOT and QSPM methods, there is a marketing strategy that can be used by companies, namely carrying out promotional and advertising activities to attract potential customers and expand the marketing area with a TAS score of 6.568.